Emergency teleorthopaedics m-health system for wireless communication links - Hadjinicolaou, Marios G.; Nilavalan, Rajagopal; Itagaki, T.; Voskarides, Sotos; Pattichis, Constantinos S.; Schizas, Akis N. (My University, 2009)
For the first time, a complete wireless and mobile emergency TeleOrthoPaedics system with field trials and expert opinion is presented. The system enables doctors in a remote area to obtain a second opinion from doctors in the hospital using secured wireless telecommunication networks. Doctors can exchange securely medical images and video as well as other important data, and thus perform remote consultations, fast and accurately using a user friendly interface, via a reliable and secure telemedicine system of low cost. The quality of the transmitted compressed (JPEG2000) images was measured using different metrics and doctors opinions. The results have shown that all metrics were within acceptable limits. The performance of the system was evaluated successfully under different wireless communication links based on real data.
Keywords: Wireless communication systems; Diagnostic imaging; Telemedicine; JPEG (Image coding standard)